Answer :

Consider sin2 θ cos2 θ (1 + tan2 θ)(1 + cot2 θ)

= sin2 θ cos2 θ (sec2 θ)(cosec2 θ) ( 1 + cot2 θ = cosec2 θ and 1 + tan2 θ = sec2 θ)


= sin2 θ (cosec2 θ) cos2 θ (sec2 θ)


= 1 × 1


= 1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses